Ice-Induced Vibration Analysis of Offshore Platform Structures Based on Cohesive Element Method - Jianhua Zhang; Xiaoyu Wang; Ke Sun; Yueqi Lai; Dianwei Gao; Won-Hee Kang; Bin Wang; Bingjun Wang (Journal of Marine Science and Engineering, 2023)
This study conducted ice-induced vibration analysis on offshore platform structures using the cohesive element method (CEM). The efficacy of this method in simulating the interaction between sea ice and the platform structure is verified by comparing it with the Hamburg Ship Modeling Pool (HSVA) ice-breaking experiment. Subsequently, the vibration response of a sea-ice-jacket platform model is investigated under both unprotected conditions and with the presence of ice-breaking cones. The findings reveal that the motion response of offshore platforms exhibits a positive correlation with the impact velocity of the ice, while the sensitivity of this impact is found to be minimal. Furthermore, the influence of different ice directions on the vibration response of offshore platforms is significant, and the shielding effect has an important impact on the platform’s response. Notably, offshore platforms equipped with 52.5-degree cones demonstrate the most effective vibration reduction, reducing the maximum acceleration by 63% compared to unprotected configurations. It is worth mentioning that as the cone angle increases, the corresponding ice-breaking cone undergoes higher load-bearing.